Gereciamento SNMP com autenticação remota: aplicação em UPSs - Silveira, Jarbas Aryel Nunes da (2006)
The reliability of a computer system is based not only on the computer itself, but also on its related power system. For that reason, more and more critical systems are counting on UPSs (Uninterruptible Power Supplies) to account for a continuous supply of power. Although the task of managing an UPS for a standalone system be quite straightforward, when it comes to computer distributed systems that task has to follow an equally distributed approach. Depending on the strategy used to manage that distributed UPS network, this task may be very complex. However, keeping in mind that most computer systems in a distributed architecture make use of TCP/IP to be logically connected, one could profit from the facilities provided by this protocol and design a management strategy that makes use of it. In fact, TCP/IP is not the only suite of protocols used to interconnect computer systems. SNMP (Single Network Management Protocol) is also frequently used as a way of managing (hardware and/or software) devices associated with computers. This dissertation proposes and implements a way of managing distributed UPSs by using SNMP, taking advantage of all the facilities furnished by the protocol. This works describes how the use of SNMP makes it possible to manage an arbitrarily number of UPSs remotely. This makes the design of UPS management systems a relatively easy task, and contributes to introduce a high degree of flexibility on the task of managing distributed UPSs. Finally, it is described how the system and tests were implemented as well as proposals for future work is presented.